Forms of Women's Resistance in the Novel “Perempuan yang Menangis kepada Bulan Hitam” and the Novel “Perempuan yang Menunggu di Lorong Menuju Laut” by Dian Purnomo - Liya Yuliyani; Agus Nuryatin; U’um Qomariyah (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
In recent years, women in Indonesia have experienced various forms of discrimination and harassment. This not only happens in real life but also happens in literary works. So, it is necessary to look further or examine the efforts made by women or women's resistance to overcome these problems. This research aims to reveal forms of women's resistance in the novel "Perempuan yang Menangis kepada Bulan Hitam" and the novel "Perempuan yang Menunggu di Lorong Menuju Laut" by Dian Purnomo. The method used in this research is descriptive qualitative using feminist literary criticism theory. Data sources were obtained from the entire contents or chapters of the two novels. Data collection techniques use reading and note-taking techniques. The technique for validating this research data is triangulation. The results of the analysis show two forms of women's resistance. Namely resistance in the form of thoughts and resistance in the form of actions. The results of the study are expected to provide knowledge to readers regarding women's resistance in literary works with feminist studies, as well as Indonesian language learning, especially literary teaching materials, and in the field of education.